Adrenal gland involvement in 11-ketotestosterone production analyzed using LC-MS/MS - Ikegawa, Kento; Hasegawa, Yukihiro (Frontiers in Endocrinology, 2023)
Introduction: 11-ketotestosterone (11KT), which is derived by the bioconversion of testosterone via 11β-hydroxytestosterone (11OHT), is a potent agonist of the human androgen receptor. The adrenal gland is considered an important organ in 11KT production because CYP11B1, which catalyzes testosterone to 11OHT, is expressed in the adrenal glands. The present study aimed to demonstrate adrenal gland involvement in 11KT production in prepubertal children, a topic which has not yet been addressed by any previous studies. Methods: Three, retrospective, observational studies were performed. Study 1 enrolled patients aged 8 months to 7 years with severe Kawasaki disease (KD) who were treated with mPSL pulse. Studies 2 and 3 included patients who had received a corticotropin-releasing hormone (CRH) stimulation test and adrenocorticotropic hormone (ACTH) stimulation test, respectively. Samples were collected before and after treatment or drug administration, and serum 11KT, 11OHT, and other 11-oxygenated androgens were measured by LC-MS/MS. Steroid hormone values before and after medication were analyzed using the Wilcoxon signed rank test. Results: Studies 1, 2, and 3 included twenty patients with severe KD, eight patients with a CRH stimulation test, and eight patients with an ACTH stimulation test, respectively. Study 1 demonstrated that the median (IQR) 11KT level was significantly higher before, than after, mPSL pulse (0.39 (0.28-0.47) nmol/L versus 0.064 (0.012-0.075) nmol/L ; P < 0.001). Studies 2 and 3 indicated no significant difference in the median 11KT value before and after the CRH or ACTH stimulation test while the 11OHT value was significantly higher after the test. Conclusion: In conclusion, the mediation of 11KT production by ACTH demonstrated the importance of the adrenal glands in the synthesis of this androgen in prepubertal children.